Primary arm spacings in unidirectionally solidified low alloy steels - (:unkn) unknown (My University, 2006)
Primary arm spacings and their morphologies in the ternary Fe - 1.6 % Mn - 0.1 to 0.75 % C alloys were investigated in quenched unidirectionally solidified specimens. The primary arms grew mainly in the so-called "close packed" arrangement and their spacing did not change with time. By increasing the growth rate and the temperature gradient in the liquid a decrease in primary arm spacings was seen. The results were compared with current primary arm models. It is seen that predictions of the Hunt and Hunt-Lu equations underestimate the experimental values whereas the Kurz-Fisher equation, Laxmanan's minimum undercooling and stability equations, Trivedi equation and Ma-Sahm equation overestimate them. Ma-Sahm's equation is modified and it is shown that this modified model can predict very closely experimental measurements and also many available experimental data in literature (122 data in thirteen different steels).
Keywords: Dendrite morphology; Microsegregation; Primary dendrite arm spacing; Steels